Are Computer-Based Treatment Programs Effective at Reducing Symptoms of Substance Misuse and Mental Health Difficulties Within Adults? A Systematic Review. Issue 4 (2nd October 2019) - Dugdale, Stephanie; Elison-Davies, Sarah; Semper, Heather; Ward, Jonathan; Davies, Glyn
Abstract: Objective: Comorbid substance misuse and mental health difficulties are recognized as a leading contributor to disease burden worldwide. Amid cuts to health care services, computer-based interventions may provide support for patients experiencing these difficulties. The aims of this systematic review were to identify and investigate the efficacy of these computer-based interventions at improving substance misuse and mental health outcomes. Methods: A systematic search was conducted of CINAHL Plus, PsycARTICLES, PsycINFO, Medline, Web of Science, and the Cochrane Library. Gray literature was also searched for relevant papers. Data were extracted from 33 papers, which met eligibility criteria by reporting a computer-based intervention designed to treat substance misuse and mental health in adults. Quality assessments were conducted on these papers. Results: Computer-based interventions generally led to an improvement of substance misuse and mental health outcomes within groups and when compared against waitlist control and psychoeducation. Computer-based interventions were effective at improving dual diagnosis outcomes, and improvements to mental health outcomes specifically were maintained for up to nine months. However, the combined effect of computer-based interventions and therapist support was found to be more effective than the effects of computer-based interventions alone. Conclusions: Many papers were limited by high attrition rates commonly attributed to "digital" interventions. Future research should consider systematically recruiting a range of participants, including those potentially affected by the digital divide, and incorporating methods within research to maintain engagement. This review was also limited by the heterogeneity of the papers reported, many of which differed between targeting dual diagnosis and targeting either substance misuse or mental health respectively, with outcomes investigating other difficulties out of curiosity.